Optimization of Liquid Organic Fertilizer from Livestock Manure with Indigofera for Hydroponic Lettuce Growth - Cintiyah, Farida; Salundik, Salundik; PDMH, Karti; Komala, Iyep (Universitas Panji Sakti, 2024)
Indonesia faces the challenge of declining agroecosystem quality due to the long-term use of synthetic chemical fertilizers, indicating the need for a transition to organic fertilizers to support sustainable agricultural practices. Therefore, this study aims to analyze the quality of liquid organic fertilizer made from dairy cow manure, laying hen manure, and Indigofera zollingeriana and to examine the effects of the combination of liquid organic fertilizer on the growth and yield of lettuce (Lactuca sativa L.). This research uses a Completely Randomized Design (CRD) experimental method with five treatments of liquid organic fertilizer (LOF) substitution and three replications to evaluate its effects on the growth and yield of hydroponic lettuce, where the data are analyzed using ANOVA and Tukey's post hoc test. The results show that the liquid organic fertilizer produced from the combination of dairy cow manure, laying hen manure, and Indigofera zollingeriana meets the quality standards of Minister of Agriculture Regulation No. 261 of 2019 with a total N content of 3.11%, P2O5 2.12%, and K2O 1.94%, and is effective in enhancing lettuce growth. The combination of liquid organic fertilizer and AB Mix, particularly AB Mix 75% + LOF 25% and AB Mix 50% + LOF 50%, results in optimal lettuce growth. Therefore, using a combination of liquid organic fertilizer and AB Mix can increase the efficiency of lettuce production in hydroponic systems and can be adopted by farmers to improve crop yields and quality.